2019
DOI: 10.21928/uhdjst.v3n1y2019.pp1-8
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Impacts of Shewashok Oil Field on Sheep and Cow Meat Using Vital Trace Elements as Contamination Bioindicators

Abstract: Air, water and food are the basic needs of most of the living organism to survive. The quality of consumed water, air and food may transfer to the consumers. Ambient environment is built base on interaction of living and non-living organism, chemical and physical compounds, thus oil field emissions, effluents and its general waste can involve. Because of gas flaring in oilfield toxic gases and particles are realised into the atmosphere. Quite possibly the particles contain heavy metals because they are driven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…A particular research regarding elevating heavy metals in crude oil workers blood confirms that Pb and Zn is quite high in their blood that possibly resulted in polluted and unprotected environment (Saleh et al, 2021). Another similar study as the current study has revealed that Hg, Al, and Fe are higher WHO standard in sheep and cow meats (Hamadamin et al, 2019).…”
Section: Study Areasupporting
confidence: 83%
“…A particular research regarding elevating heavy metals in crude oil workers blood confirms that Pb and Zn is quite high in their blood that possibly resulted in polluted and unprotected environment (Saleh et al, 2021). Another similar study as the current study has revealed that Hg, Al, and Fe are higher WHO standard in sheep and cow meats (Hamadamin et al, 2019).…”
Section: Study Areasupporting
confidence: 83%
“…Since then, the product has mostly been sold both to the export market and local markets. In 2014, a new KRG pipeline became operational allowing export all the way to the Turkish port of Ceyhan.Althoug, in 2018, the Taq Taq oil Field had already 31 wells drilled, it has produced more than 180 MMbbl to date (Hamadamin, et al, 2019). At present about 6 villages around Taq Taq Oil Field has more than 1500 inhabitants.…”
mentioning
confidence: 99%